2005
DOI: 10.2174/0929867053507261
|View full text |Cite
|
Sign up to set email alerts
|

Yeast System as a Screening Tool for Pharmacological Assessment of G Protein Coupled Receptors

Abstract: G-protein-coupled receptors (GPCRs) constitute the largest but the most divergent class of cell surface proteins. Although they are thought to share a common 3D-structure composed of seven transmembrane helical domains, they can be activated by extracellular signals as diverse as light, peptides, proteins, lipids, organic odorants, taste molecules, nucleotides or nucleosides. They are involved in an extraordinarily large number of physiological functions and are therefore potential drug targets for many human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 66 publications
0
69
0
2
Order By: Relevance
“…During the last decade various GPCRs have been successfully expressed in S. cerevisiae (Minic et al, 2005). Yeast is an attractive expression system because it offers the genetic engineering tools typical of a microorganism, while possessing an eukaryotic type of secretory pathway and post-translational machinery.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade various GPCRs have been successfully expressed in S. cerevisiae (Minic et al, 2005). Yeast is an attractive expression system because it offers the genetic engineering tools typical of a microorganism, while possessing an eukaryotic type of secretory pathway and post-translational machinery.…”
Section: Introductionmentioning
confidence: 99%
“…Saccharomyces cerevisiae, referred to as yeast hereafter, has emerged as an important organism for the study of heterologously expressed GPCRs (21,22). Functional expression of heterotrimeric GPCRs can be achieved by linking the expressed receptor to the endogenous pheromone response pathway, which has been performed for analysis of multiple mammalian GPCRs (22) and some invertebrate GPCRs (23)(24)(25). Previously, we have reported the expression of Pa oa1 in yeast, which resulted in a ligand-independent (constitutive) expression system (25).…”
mentioning
confidence: 99%
“…Because it was found that pH-sensing pathways also control the expression of virulence traits not directly associated with pH, including adhesion to host cells and tissue invasion (Davis, 2009), further studies would be warranted. Because of the high homology between the yeast pheromone signalling pathway and that of mammalian GPCRs and their easy genetic modulation, they were even used in reporter assays to screen for new drugs targeting GPCRs (Minic et al, 2005), thus underlining the evolutionary conserved use of GPCRs for sensing and signalling of distinct cues among kingdoms.…”
Section: Sensing Of Physical Cuesmentioning
confidence: 99%